Indirect measurement of photosynthetic pigments in the leaves of Jatropha curcas - Rigon, João Paulo Gonsiorkiewicz [UNESP]; Capuani, Silvia [UNESP]; De Brito Neto, José Félix; De Macêdo Beltrão, Napoleão Esberard (Universidade Estadual de Londrina, 2013)
The aim of this work was to generate mathematical models capable of identifying photosynthetic pigments and soluble proteins from the leaves of Jatropha curcas using the relationship between classical readings performed by spectrophotometry and the chlorophyll meter, ClorofiLOG ® 1030. The work was conducted at Embrapa Cotton, in the city of Campina Grande, state of Paraíba, Brazil. For indirect analysis, portable equipment was used to read leaf discs at different stages of development. The chlorophyll in these discs was then determined using a classical method, while the Bradford method was used to determine soluble proteins. The data were subjected to analysis of variance and regression analyses, in which the readings obtained using the portable chlorophyll meter were the dependent variables and the photosynthetic pigments and soluble protein determined by the classical method the independents variables. The results indicated that with the exception of chlorophyll b and soluble protein, the mathematical models obtained with the portable chlorophyll ClorofiLOG ® 1030 can be used to estimate the concentration of photosynthetic pigments with high precision, thus saving time and the chemical reagents required for conventional procedures.
Keywords: Calibration; Chlorophyll; Chlorophyll meter; Soluble protein